The renminbi rises : myths, hypes and realities of RMB internationalisation and reforms in the post-crisis world - Lo, Chi, 1960- (Houndmills, Basingstoke, Hampshire : Palgrave Macmillan, 2013)
'Until recently the world has been relying on the US dollar and the Euro to lubricate the flow of global trade and finance. A newcomer, the Renminbi (RMB) or Chinese Yuan, joined the global monetary system in 2000. The rise of the RMB is both an indicator and a result of the evolution in the global macro landscape that shifts economic weight from the developed markets, led by Europe, Japan and the US, to the emerging markets, led by China.Research on RMB internationalisation is difficult because events have been unfolding fast, with frequent shifting regulations. Most financial market research is sales-driven, shallow and without serious investigation into the structural underpinning of events. Most crucially, there has been insufficient systematic research on the structural realities behind the RMB internationalisation exercise. No-one has openly questioned the credibility of the RMB as an international currency. This is the first book to address these issues by focusing on the structural factors behind the rise of the RMB. It uses a critical approach, questioning conventional wisdom and the status quo to anslyse China's currency ambition in the post-subprime world. Discussions combine rigorous research thoughts, data, facts and economic logic with real world issues to elaborate on the arguments and make them reader-friendly.'--
Machine generated contents note: -- 1. Renminibi Shakes up Global Currencies -- 2. A Not So Mighty Yuan -- 3. From Money to RMB-nisation -- 4. Trade is Not Enough -- 5. The Next Steps for Internationalisation -- 6. China Ready for a Globalised RMB? -- 7. Creeping Reforms Raise Systemic Risk -- 8. RMB-nisation Needs Offshore Market -- 9. RMB the Third Major Reserve Currency -- 10. The Reality Behind RMB-nisation.
Includes bibliographical references (pages 186-189) and index.
Keywords: Renminbi; Money -- China; International finance